KINEMATIC STRUCTURE OF THE SLOW FOX FEATHER STEP - Ol`ga Kyselovičová; Milan Špánik (Exercise and Quality of Life)
In dance, biomechanical methodologies are used to improve aspects of dance technique. Therefore the aim of our study was to gain knowledge of the kinematic structure of the feather step in slow fox routine. Material and methods: Four top level dance couples were involved in the study. To examine the routine biomechanically we have filmed the particular dance figures by high speed camera with frequency of 50 frames per second. Subsequently, we processed and evaluated digitalized images by 2D analysis. The path of gravity and angular changes in knee joint in the particular dance figures phases were evaluated and compared between partners and pairs together. Results: Dancing couples in the same conditions reached different readings in angle of the knee joint as well as trajectory of the centre of gravity during motion.